Comparative evaluation of nutrient utilization, growth performance and methane emission in Murrah buffaloes, Vrindavani and Tharparkar cattle fed on a similar diet - RATHODE, NARAYANA; VERMA, A K; KALA, ANJU; CHATURVEDI, V B; H, RAHMAN; CHAUDHARY, L C (The Indian Journal of Animal Sciences, 2024)
Present study was conducted to compare the indigenous, crossbred cattle and buffaloes for the utilization of nutrients, growth and methane emission when fed on a similar diet. A 120-days feeding trial was carried out with six animals each of Murrah buffalo, Vrindavani and Tharparkar cattle, each on a similar diet comprising of wheat straw 30% and concentrate 70%. The DM intake (kg/d) was significantly higher for Vrindavani cattle than Murrah buffaloes and Tharparkar cattle. Whereas, the apparent digestibility of nutrients was similar in all the groups. Average daily gain (g/d) was higher in Murrah buffaloes than Vrindavani and Tharparkar cattle. Higher feed conversion ratio was seen in Vrindavani than other two groups which indicate that the Murrah and Tharparkar have better feed efficiency than Vrindavani. The N balance was significantly higher in Murrah followed by Vrindavani and was lowest in Tharparkar. The methane emission (l/kg DMI, l/kg DDMI) was similar among the three groups. It was concluded that Vrindavani cattle showed higher feed conversion ratio than buffaloes and Tharparkar cattle, which signifies later two species are superior in nutrient utilization than former one. In terms of methane production and digestibility of nutrients, the animals of all three groups were similar.